Comparison of ophthalmic artery Doppler velocimetry changes on patients with hypertensive disorders of pregnancy versus normotensive pregnant women in third trimester of pregnancy: A prospective study - Suma K. B; Anupama Marnal B A; Mamatha S; Vikram Patil; Shweta R. Poojary; Sumuk M S (Journal of Krishna Institute of Medical Sciences University)
Background: Hypertensive disorders in pregnancy are widely acknowledged as among the most severe complications, significantly impacting maternal as well as neonatal morbidity and mortality rates globally. Preeclampsia is the most important gestational condition associated with hypertension. Aim and Objectives: To compare Ophthalmic Artery Doppler (OAD) indices of normotensive and hypertensive pregnant women in third trimester of pregnancy and to correlate the OAD changes with the severity of hypertensive disorder of pregnancy in third trimester. Material and Methods: A prospective study was conducted in a tertiary care hospital, Mysuru. Seventy pregnant women with hypertensive disorders and 70 normotensive pregnant women were enrolled in this study during their third trimester. A comprehensive history of hypertension was obtained, and an obstetric scan was conducted to assess the gestational age. Doppler examinations of the umbilical, middle cerebral, and uterine arteries were also performed. At the same time, maternal ophthalmic artery Doppler readings were obtained, and the women were monitored after birth. The perinatal outcomes were also documented. Results: Statistically significant differences were observed in ophthalmic artery Doppler parameters' mean values between normotensive women and those with hypertensive disorders of pregnancy, particularly for peak systolic velocity, pulsatility index, and resistivity index. Conclusion: Pregnancy complicated by hypertensive disorders showed significant differences in ophthalmic artery Doppler velocities between women with preeclampsia and healthy pregnant women. These findings imply that ophthalmic artery Doppler parameters can be considered predictable indicators of the development of preeclampsia. These parameters, which include safety, cost-effectiveness, and accessibility, can be used to distinguish between preeclamptic and normotensive pregnancies during late gestation.